(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Man-woman relationship is a man-made relationship and it is the basis of all other relationships. Indian woman occupies an important place in all human relationships. Outwardly, man-woman relationship appears to be based on mutual love and trust and understanding, but inwardly it is marred by the evils such as male ego male- domination and gender discrimination. There has often been a conflict in a man-woman relationship as the man doesn’t find both, the mother and the sweetheart in one and the same person. As an Indian English novelist, Shashi Deshpande concretizes in her fiction the major themes such as man-woman relationship, gender discriminations, marginalization, rebellion and protest. To vindicate and authenticate her selfhood and self-expression, she insisted on being called simply ‘a writer’ and not a ‘woman writer’ much less ‘a feminist writer’. She maintains that she writes about relationships, and that she should not be evaluated by gender, and that her authorial position stays beyond male or female dichotomy.